Nucleation Processes at Condensation of Amorphous Chalcogenide Semiconductor Films - A.V. Dalekorey; V.P Ivanitsky; V.S. Kovtunenko; R.O. Meshko (Журнал нано- та електронної фізики)
The initial stages of nucleation of amorphous chalcogenide semiconductor films were investigated theoretically and experimentally. The important role of the complex mass spectrometry of the vapor phase in the process of nucleation and growth of amorphous chalcogenides island on uniform substrate surface was found.